Processed carp scales as a functional food for sepsis protection: enhancing amino acid content and bioactive peptide profiles - Yan, Lisha; Wang, Qiong; Tang, Min (Frontiers in Nutrition, 2026)
Carp scales represent an abundant and protein-rich by-product of aquaculture that is commonly discarded as waste. Despite their potential as a sustainable source of dietary protein, their rigid structural matrix restricts nutrient bioavailability. Moreover, sepsis-induced multiorgan injury remains a life-threatening clinical condition with high mortality, underscoring the need for novel functional nutritional strategies. Although traditional processing methods are known to alter physical properties, their effects on the nutritional composition and anti-inflammatory activity of carp scales remain poorly understood. This study aims to characterize the compositional changes induced by thermal processing and to evaluate the enhanced protective efficacy of processed versus raw carp scales in a sepsis model. Processed carp scales were prepared using optimized sand stir-frying (150 °C, 2.5 min) and evaluated through comparative analyses integrating LPS-induced sepsis models and in vivo experiments. Results demonstrated that thermal processing induced significant biochemical transformations, markedly improving the nutritional profile by increasing total protein content and amino acid availability. Notably, LC–MS analysis identified 10 novel bioactive peptides (e.g., PGSPGPAGPAGARGQQ) uniquely generated during heating. Pharmacologically, processed carp scales exhibited superior therapeutic effects compared to raw scales. In vivo, treatment with processed carp scales significantly suppressed pro-inflammatory cytokines (TNF-α, IL-6, IL-1β), effectively attenuated multiple organ dysfunction—evidenced by reduced ALT, AST, and BUN levels—and normalized coagulation parameters while alleviating histopathological damage. This study reveals a “processing–nutrient–efficacy” axis, demonstrating that thermal processing generates bioactive peptides that may contribute to enhanced anti-sepsis activity. These findings support the potential of processed carp scales as a promising high-value functional food ingredient.